Aktivitas Antibakteri dan Antifungi Ekstrak Etil Asetat dengan N-Heksan Daun Nyirih ( Xylocarpus granatum) - Suhaera Suhaera; Mawardi Badar; Nurelita Nurelita (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2022)
Medicinal plants are very popular among Indonesian people as ingredients for traditional medicine. One of the medicinal plants is Nyirih (Xylocarpus granatum) from the Meliaceae family which is empirically used as a diarrhea medicine and wound cleanser. This study aimed to determine the antibacterial activity of ethyl acetate and n-hexane extract of Nyirih (Xylocarpus granatum) against Pseudomonas aeruginosa, Sthapylococcus aureus bacteria and the fungus Candida albicans. The method used is the paper disc diffusion method with a concentration of Nyirih leaves at 50%, 75%, and 100%. The results of antibacterial activity of the ethyl acetate extract of Nyirih leaves against Pseudomonas aeruginosa and Sthapylococcus aureus bacteria resulted in a DDH value (diameter of the inhibition zone) 9.83 mm - 21.28 mm, but for n-hexane extract did not produce a DDH value. The test results for antifungal activity of extract ethyl acetate and n-heksan of Nyirih leaves against Candida albicans did not produce a DDH value (diameter of the inhibition zone). Ethyl acetate extract of Nyirih leaves has potential as an antibacterial.